Optimasi Rasio Ekstrak Bahan Organik Alami dalam Formulasi Media Kultur untuk Regenerasi In Vitro Aglonema Varietas Red Borju - Permata, Citra; Kartika, Ikhsan (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aimed to optimize the ratio of natural organic extracts derived from shallot (Allium cepa) and mung bean sprouts (Phaseolus radiatus) in culture media formulations to enhance in vitro regeneration of Aglonema cv. Red Borju. These organic materials are known to contain natural phytohormones, such as auxins and cytokinins, as well as other bioactive compounds that potentially stimulate morphogenesis. The experiment was conducted using several extract ratio treatments incorporated into Murashige and Skoog (MS) basal medium. Growth responses were evaluated based on plantlet height, number of leaves, number of roots, fresh weight, and dry weight. The results demonstrated that variations in extract ratios significantly affected plantlet growth performance. The combination of shallot and mung bean sprout extracts at a ratio of 2:1 produced the most significant improvement in all observed growth parameters. The use of natural organic extracts proved to be an effective alternative to partially replace synthetic components in culture media without reducing growth efficiency. This study contributes to the development of environmentally friendly and cost-effective in vitro culture techniques for the mass propagation of Aglonema cv. Red Borju.